Suture - Phantasmen der Vollkommenheit. - Eiblmayr, Silvia (Salzburg : Salzburger Kunstverein, 1994)
Barney, Matthew ; Birnbaum, Dara ; Bloom, Barbara ; Boehme, Max ; Eva & Adele ; Fox, Judy ; Ganahl, Rainer ; Gotscho ; Hahnenkamp, Maria ; Kandl, Johanna ; Krystufek, Elke ; van Lamsweerde, Inez ; Miller, John ; Orlan ; Rist, Pippilotti ; Ruggeri, Laura ; Sherman, Cindy ; Siem, Wiebke ; Trockel, Rosemarie ; Turk, Herwig
Suture - Phantasmen der Vollkommenheit, Salzburger Kunstverein, Salzburg, 20. April - 29. Mai 1994
boek